Case Report: Spontaneous regression of extruded lumbar disc herniation following Chuzhen therapy over 3 years - Hu, Youpeng; Wang, Ye-Hui; Guo, Wenlong; Zhao, Shengxin; Qing, Peidong; Xie, Shiming; Fan, Xiaohong (Frontiers in Medicine, 2025)
BackgroundLumbar disc herniation (LDH) is a common disease, and most cases can be satisfactorily treated with conservative therapy. Chuzhen therapy, a non-surgical, non-pharmacological, and non-invasive therapy, can be performed at home, making it more acceptable to patients. However, evidence supporting the efficacy of this therapy for the treatment of acute LDH is limited.Case presentationWe report a 50-year-old male who presented with lower back pain, persistent radiating pain, and numbness in the lower extremities. Computed tomography (CT) imaging revealed a large right-sided protruding nucleus pulposus (PNP) at the L5/S1 level, compressing the nerve root. The patient experienced significant symptomatic relief after 1 month of outpatient Chuzhen therapy followed by 3 years of home-based Chuzhen therapy. Follow-up imaging conducted 3 years later showed a remarkable regression of the herniated nucleus pulposus, with a substantial 64.8% reduction in its size. Concurrently, the patient's LDH classification was downgraded from MSU3-AB to MSU2-A.ConclusionsWe report for the first time a case of LDH treated at home with Chuzhen therapy, which resulted in disc retraction. In this case, Chuzhen therapy was safe and effective as a monotherapy, but more conclusive and effective evidence is needed to elucidate its specific therapeutic mechanism.